Alternative Splicing of Putative Stroke/Vascular Risk Factor Genes Expressed in Blood Following Ischemic Stroke Is Sexually Dimorphic and Cause-Specific - Dykstra-Aiello, Cheryl; Sharp, Frank R.; Jickling, Glen C.; Hull, Heather; Hamade, Farah; Shroff, Natasha; Durocher, Marc; Cheng, Xiyuan; Zhan, Xinhua; Liu, DaZhi; Ander, Bradley P.; Stamova, Boryana S. (Frontiers in Neurology, 2020)
Genome-wide association studies have identified putative ischemic stroke risk genes, yet, their expression after stroke is unexplored in spite of growing interest in elucidating their specific role and identifying candidate genes for stroke treatment. Thus, we took an exploratory approach to investigate sexual dimorphism, alternative splicing, and etiology in putative risk gene expression in blood following cardioembolic, atherosclerotic large vessel disease and small vessel disease/lacunar causes of ischemic stroke in each sex compared to controls. Whole transcriptome arrays assessed 71 putative stroke/vascular risk factor genes for blood RNA expression at gene-, exon-, and alternative splicing-levels. Male (n=122) and female (n=123) stroke and control volunteers from three university medical centers were matched for race, age, vascular risk factors, and blood draw time since stroke onset. Exclusion criteria included: previous stroke, drug abuse, subarachnoid or intracerebral hemorrhage, hemorrhagic transformation, infection, dialysis, cancer, hematological abnormalities, thrombolytics, anticoagulants or immunosuppressants. Significant differential gene expression (fold change > |1.2|, p < 0.05, partial correlation > |0.4|) and alternative splicing (false discovery rate p-value < 0.3) were assessed. At gene level, few were differentially expressed: ALDH2, ALOX5AP, F13A1, and IMPA2 (males, all stroke); ITGB3 (females, cardioembolic); ADD1 (males, atherosclerotic); F13A1, IMPA2 (males, lacunar); and WNK1 (females, lacunar). GP1BA and ITGA2B were alternatively spliced in both sexes (all patients versus controls). Six genes in males, five in females, were alternatively spliced in all stroke compared to controls. Alternative splicing and exon-level analyses associated many genes with specific etiology in either sex. Of 71 genes, 70 had differential exon-level expression in stroke patients compared to control subjects. Among stroke patients, 24 genes represented by differentially expressed exons were male-specific, six were common between sexes, and two were female-specific. In lacunar stroke, expression of 19 differentially expressed exons representing six genes (ADD1, NINJ2, PCSK9, PEMT, SMARCA4, WNK1) decreased in males and increased in females. Results demonstrate alternative splicing and sexually dimorphic expression of most putative risk genes in stroke patients’ blood. Since expression was also often cause-specific, sex and etiology are factors to consider in stroke treatment trials and genetic association studies as society trends towards more personalized medicine.